A comparative study of ferric carboxymaltose and iron sucrose as a parenteral iron treatment in iron deficiency anaemia during pregnancy - Patel, Alpesh R.; Patel, Vipul S.; Patel, Parth R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Iron deficiency anemia during pregnancy is a serious global concern specially in developing country, which is preventable with effective measures. In women who cannot tolerate oral iron or have moderate to severe anemia, parenteral iron in the form of iron sucrose or ferric carboxymaltose can be very much useful. This study aimed to compare efficacy and safety of iron sucrose and ferric carboxymaltose in iron deficiency anemia during pregnancy. Methods: This prospective interventional comparative study was conducted during May 2016 to April 2018 at tertiary care hospital and total 100 antenatal women from 28 to 34 weeks of gestation having moderate to severe anemia were included in this study and all women were divided in to 2 groups randomly and were given either iron sucrose or ferric carboxymaltose according to iron requirement. Rise in haemoglobin and serum ferritin were noted and data analysed statistically. Results: The mean rise of haemoglobin with iron sucrose was 1.8 gm% and with ferric carboxymaltose was 2.6 gm%. The mean rise of serum ferritin with iron sucrose was 82.4 ng/ml and with ferric carboxymaltose was 100.9 ng/ml. Other than minimal local reaction one woman had developed severe anaphylactic reaction after receiving iron sucrose. Conclusions: Intravenous ferric carboxymaltose is better and safe molecule than iron sucrose and it has advantage of ability to administer large dose in single sitting which reduce overall cost of therapy. Hence ferric carboxymaltose is a drug of choice as parenteral iron therapy in iron deficiency anemia during second trimester of pregnancy.